A proposed set of standards and requirements for education and training of law librarians in the Philippines - Malig, Rollyn G. (2001)
Law books and materials are in one way or another different considering that law is clearly a very specialized and technical field or subject matter. Thus, it would follow that it would require special skills, knowledge and training for an efficient and well-organized search to take place. This is where the law librarian comes in. He/She embraces not only academic law librarians, practice librarians, librarians in industry and commerce but also information officers and managers, documentalists and other suppliers of legal literature and reference materials. Supposedly armed with an adequate and ample knowledge of law and its sources, he or she provides his or her expertise in legal bibliography and research. Those who wish to enter into law librarianship would discover that it would be almost impossible to do so without having at least a basic knowledge of the law itself. Furthermore, inadequacy or total lack of knowledge in the subject would jeopardize the basic aim of the library and the librarian in providing information and sources of information to the user in a timely and efficient manner.